(untitled)
We study the following mean field equation Δ_gu+ρ(e^u _S^2 e^udμ-14π)=0 in S^2, where ρ is a real parameter. We obtain the existence of multiple axially asymmetric solutions bifurcating from u=0 at the values ρ=4n(n+1)π for any odd integer n≥3. , number=1, journal=Analysis in Theory and Applications, year=2022, month=Dec., pages=19–32